2022
DOI: 10.3390/ijerph19031344
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Assessment Tool (BAT): Validity Evidence from Brazil and Portugal

Abstract: The Burnout Assessment Tool (BAT) has been gaining increased attention as a sound and innovative instrument in its conceptualization of burnout. BAT has been adapted for several countries, revealing promising validity evidence. This paper aims to present the psychometric properties of the Brazilian and Portuguese versions of the BAT in both the 23-item and 12-item versions. BAT’s validity evidence based on the internal structure (dimensionality, reliability, and measurement invariance) and validity evidence ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 105 publications
(127 reference statements)
5
28
0
3
Order By: Relevance
“…The BAT-C short version worked similarly among male and female students and working and non-working student groups, according to Zumbo and Koh’s [ 79 ] invariance test indices. Furthermore, the results concerning the measurement invariance across gender align with those recently reported by Sinval et al [ 80 ] in their validation study of the BAT-C short version in a sample of Portuguese and Brazilian workers. Nonetheless, the current study is the first one to test the measurement invariance of the BAT-C short version across gender in a sample of university students.…”
Section: Discussionsupporting
confidence: 88%
“…The BAT-C short version worked similarly among male and female students and working and non-working student groups, according to Zumbo and Koh’s [ 79 ] invariance test indices. Furthermore, the results concerning the measurement invariance across gender align with those recently reported by Sinval et al [ 80 ] in their validation study of the BAT-C short version in a sample of Portuguese and Brazilian workers. Nonetheless, the current study is the first one to test the measurement invariance of the BAT-C short version across gender in a sample of university students.…”
Section: Discussionsupporting
confidence: 88%
“…This questionnaire conceives burnout as a syndrome, meaning that its four components (exhaustion, mental distance, and cognitive and emotional impairment) are interrelated and refer to a common underlying condition (15). This implies that in addition to subscale scores also a composite, overall burnout score can be used (8,(16)(17)(18)(19). We analyzed samples from three different European countries: The Netherlands, Belgium (Flanders) and Finland.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the MBI, the BAT fulfills the measurement criteria according to the Rasch model and can therefore be considered a one-dimensional measure of burnout (15)(16)(17). This means that burnout, as assessed with the BAT, can be considered as syndrome; a set of four associated symptoms that occur together and refer to the same underlying condition.…”
Section: Scand J Work Environ Health -Online Firstmentioning
confidence: 99%
“…The original version of BAT included 33 items measuring the core components (23 items) and the secondary symptoms (10 items). BAT has been translated and validated across several countries [ 14 , 15 ] and beyond [ 16 , 17 , 18 ]. Consiglio, Mazzetti, and Schaufeli empirically supported the reliability and factor validity of the Italian version of BAT and the convergent and discriminant validity compared to MBI [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research using the JD-R model has shown that BAT scores are positively associated with job demands across several countries (i.e., Japan, the Netherlands, and Belgium) [ 14 , 18 ]. Simultaneously, core symptoms of burnout report a reversed association with job resources (e.g., role clarity), personal resources (e.g., self-efficacy), and positive work-related attitudes (e.g., organizational commitment) [ 41 ].…”
Section: Introductionmentioning
confidence: 99%